Utility of red cell distribution width in screening for iron deficiency. Issue 7 (22nd May 2013) - Hinchliffe, Roderick F; Bellamy, Graham J; Finn, Adam; Bell, Frank; Vora, Ajay J; Lennard, Lynne
Abstract : Aims: To assess the sensitivity of an adult-derived red cell distribution width (RDW) reference limit in the detection of iron deficiency in young children. Methods: Haematological analysis performed on a cohort of 13-month-old healthy term infants of North European ancestry. Results: 21/98 infants were iron-deficient (>2.5% hypochromic red cells). Of the remaining 77, 35 with RDW >13.9% also had evidence of incipient iron deficiency on the basis of significantly lower haemoglobin (11.5 vs 11.8 g/dl, p=0.046), mean cell volume (75.6 vs 77.8 fl, p=0.002) and mean cell haemoglobin (25.4 vs 26.2 pg, p=0.002) values and higher zinc protoporphyrin (55 vs 44 μmol/molhaem, p<0.001) values than those of the 42 with RDW ≤13.9%. Conclusions: An adult-derived RDW reference limit has utility in screening for iron deficiency at the age of 13 months. The incidence of non-anaemic iron deficiency in this group was 52.8%.